The composition of the egg-parasitoid guild of the golden egg bug, Phyllomorpha laciniata (Heteroptera: Coreidae), in Spain - Carrasco, David; Várkonyi, Gergely (Entomologica Fennica, 2012)
The golden egg bug (Phyllomorpha laciniata (Villers)) is a phytophagous insect with an unusual reproductive system. Females use the bodies of conspecifics, both males and females, as oviposition substrates. In addition, a varying fraction of the eggs is laid on the food plant. Egg carrying on conspecifics increases offspring survival. Predators and, especially, hymenopteran parasitoids are themain cause of egg mortality. So far, only the wasp Gryon bolivari (Giard) (Hymenoptera: Scelionidae) has been reported as an egg parasitoid of P. laciniata in several Mediterranean populations. In this study, three new egg-parasitoid species are recorded from P. laciniata: the primary solitary parasitoids Gryon monspeliense (Picard) and Telenomus sp. (Hymenoptera: Scelionidae), and the facultative hyperparasitoid Ooencyrtus telenomicida (Vassiliev) (Hymenoptera: Encyrtidae). All of these parasitoids have been reared from host eggs being carried by conspecific bugs. We discuss the taxonomy and biology of the individual parasitoid species, as well as ecological and evolutionary aspects of the interactions in this host-parasitoid system.